2012
DOI: 10.1111/j.1479-828x.2012.01461.x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer incidence and mortality in Fiji 2003–2009

Abstract: Cervical cancer screening in Fiji needs to be expanded and strengthened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Previous estimates of annual cervical cancer incidence from the Fiji Cancer Registry found women aged 35-54 had annual incidence of 0.65/1000 (2003)(2004)(2005)(2006)(2007)(2008)(2009) (Kuehn et al, 2012), although from histopathology only prior to 2010. This is lower than the finding of 1.02/1000 (in one year) from this study of women 30-49 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous estimates of annual cervical cancer incidence from the Fiji Cancer Registry found women aged 35-54 had annual incidence of 0.65/1000 (2003)(2004)(2005)(2006)(2007)(2008)(2009) (Kuehn et al, 2012), although from histopathology only prior to 2010. This is lower than the finding of 1.02/1000 (in one year) from this study of women 30-49 years.…”
Section: Discussionmentioning
confidence: 99%
“…Fiji has one of the highest incidences of cervical cancer in the Pacific region (Kuehn et al, 2012;Foliaki et al, 2011). In 2012, cervical cancer was the second most common cause of death among Fijian women, after breast cancer (Ferlay et al, 2013) and no decline in mortality has occurred since 2000 (Kuehn et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…One study from Fiji found significantly different incidence and mortality among ethnic Fijian compared to ethnic Indian women living in Fiji. The age-standardized incidence and mortality per 100,000 per year was 34.7 (95% CI: 31.0-38.5) and 33.9 (95% CI: 29.4-38.3) among ethnic Fijian women respectively, and 24.0 (95% CI: 20.4-27.6) and 13.0 (95% CI: 10.0-16.1) among ethnic Indian women, respectively (Kuehn et al, 2012). Two other studies from Fiji found similar, significant differences between ethic Fijian and ethnic Indian women living in Fiji (Law et al, 2013;Vodonaivalu and Bullen, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…However, in three studies from Fiji the country specific incidence estimates were lower than the IARC estimate (Parkin et al, 2008;Kuehn et al, 2012;Law et al, 2013). The lower incidence estimates in two of the studies from Fiji (Kuehn et al, 2012;Law et al, 2013) (Parkin et al, 2008(Parkin et al, ) 20.9 18.7 (2002 (Parkin et al, 2008(Parkin et al, ) 50.7 (2002 (Foliaki et al, 2011) 23.9 (2003-09) (Kuehn et al, 2012(Kuehn et al, ) 27.6 (2003 (Kuehn et al, 2012) 20.8 (2004-07) (Law et al, 2013(Law et al, ) 29.7 (2004 (Law et al, 2013) Papua New Guinea 34.5 40.4 (2002) (Parkin et al, 2008) 21. been due to that these studies included the time frame of 2005 and 2006 with probable substantial under-reporting to the national registries, due to a military coup and general turmoil in the country. An alternative explanation for the lower incidence rate found by these two studies from Fiji could be that the studies using hospital based data had improved ability to identify double reported cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation